Parent perspectives on the benefits and risks of child-livestock interactions - Klataske, Ryan T.; Durbin, Trevor J.; Barnes, Kathrine L.; Koshalek, Kyle; Bendixsen, Casper G. (Frontiers in Public Health, 2023)
Growing up on a farm or ranch often involves interactions with livestock that present both potential risks and benefits to children. While these “child-livestock interactions” contribute to the burden of agriculturally related injuries to youth in the United States, they may also result in improved immunological health and other benefits. Agricultural upbringings are also widely perceived to improve physical, cognitive, and skill development of children, contributing to a combination of potential benefits and risks known as the “farm kid paradox.” Although previous studies show the health impacts of child-livestock interactions, less is known about the ways in which farm and ranch parents perceive the benefits and risks of these interactions, and how and why they choose to raise children around livestock. Our research addresses this gap by analyzing data from semi-structured interviews with 30 parents of children between the ages of 10-18 who produce beef cattle in Kansas. This research is part of a larger anthropological study of the benefits and risks of child-livestock interactions involving parents on beef and dairy operations in multiple states, along with agricultural safety and health professionals. The results offer insights into the experiences, practices, and perspectives of parents, outlining agricultural ways of life in which safety and relations to risk are shaped by patterns of production, family dynamics, values and habits, and other social and cultural dimensions. These insights deepen our understanding of parents’ perceptions of both benefits and risks of agricultural childhoods.